2022
DOI: 10.1111/hex.13584
|View full text |Cite
|
Sign up to set email alerts
|

Mixed methods evaluation to explore participant experiences of a pilot randomized trial to facilitate self‐management of people living with stroke: Inspiring virtual enabled resources following vascular events (iVERVE)

Abstract: Introduction Despite digital health tools being popular for supporting self‐management of chronic diseases, little research has been undertaken on stroke. We developed and pilot tested, using a randomized controlled design, a multicomponent digital health programme, known as Inspiring Virtual Enabled Resources following Vascular Events (iVERVE), to improve self‐management after stroke. The 4‐week trial incorporated facilitated person‐centred goal setting, with those in the intervention group recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…32,33 Three qualitative assessments 25,36,37 and 2 mixed-methods studies explored the participants’ experiences with the mHealth intervention. 38,39 Participant feedback indicated a high level of acceptability for the different mHealth delivery methods, and the use of mHealth interventions to support secondary prevention of stroke. Additionally, feedback on health care provider experiences was reported in 2 publications, finding the interventions could improve provider confidence and facilitate standardized practice, 39 but continued efforts to provide support to participants were required, and longer study durations may have yielded greater benefits.…”
Section: Resultsmentioning
confidence: 99%
“…32,33 Three qualitative assessments 25,36,37 and 2 mixed-methods studies explored the participants’ experiences with the mHealth intervention. 38,39 Participant feedback indicated a high level of acceptability for the different mHealth delivery methods, and the use of mHealth interventions to support secondary prevention of stroke. Additionally, feedback on health care provider experiences was reported in 2 publications, finding the interventions could improve provider confidence and facilitate standardized practice, 39 but continued efforts to provide support to participants were required, and longer study durations may have yielded greater benefits.…”
Section: Resultsmentioning
confidence: 99%
“…A potential limitation was that we did not conduct qualitative interviews with participants as part of the phase II evaluation to determine whether the discharge support package was person-centred. However, the qualitative feedback from development of the goal-setting package and the preliminary testing of the intervention [ 22 , 36 ] indicated that the goal-setting menu provided an opportunity for the participant to reflect on what was important to them and the health professionals were supportive in guiding the process for developing their goals. Qualitative feedback from participants will be collected in the phase III testing of ReCAPS.…”
Section: Discussionmentioning
confidence: 99%
“…The ReCAPS trial (Recovery-Focused Community Support to Avoid Readmissions and Improve Participation After Stroke) 93 is currently in progress after the successful development and feasibility testing of a co-designed novel electronic communication technology intervention to support the transition to home after an acute stroke. 83,94,95 The eHealth intervention is designed to provide a range of messages sent via SMS or email to support person-centered goal attainment, self-management support and secondary stroke prevention. The intervention group receives 12 weeks of personalized, goal-centered, and administrative electronic messages, while the control group only receives administrative messages.…”
Section: Example Stroke Intervention Studies Relevant To Transitional...mentioning
confidence: 99%